Optimalisasi Perpanjangan Masa Berlaku Safe Manning di PT. Wasesa Line - Gery Lodres Simarmata; Santun Irawan; Stevian G.A. Rakka (KALAO'S MARITIME JOURNAL, 2025)
Indonesia, as the largest archipelagic country in the world, has inter-island waters that are part of the sovereign territory of the Republic of Indonesia, in accordance with the provisions of Law Number 17 of 2008 concerning Shipping. This law covers various regulations related to maritime activity standards, including safe manning. Safe manning is the determination of the minimum number of vessels on duty required to ensure the safe and effective operation of a vessel. The purpose of implementing safe manning is to maintain the safety of the vessel, passengers, and cargo, and to prevent accidents or incidents at sea. This study aims to highlight the important role of optimizing safe manning in shipping safety. Optimizing the validity period of safe manning documents can help shipowners or charterers save costs, especially in managing ship documents. It also ensures that the required number of crew members complies with applicable standards and is well-trained to handle situations that occur during shipping. Furthermore, safe manning is not only related to the number of crew members, but must also comply with the training and certification standards stipulated in the STCW Convention issued by the International Maritime Organization (IMO). With the implementation of this system, it is hoped that all parties involved in shipping operations will be able to manage ship documents more efficiently while simultaneously improving shipping safety. This innovation will provide significant benefits for shipowners in maintaining the operational quality of their vessels. Optimizing safe manning can also reduce legal risks and enhance the shipping company's reputation in the eyes of regulators and clients. By consistently implementing this standard, companies can improve operational efficiency while remaining compliant with applicable international regulations.